Penguatan Kapasitas SDM Masyarakat Desa Marapit Melalui Pendidikan Tinggi - I Ketut Soter; Putu Wisnu Saputra; I Gede Dharman Gunawan; Lamri Lamri; Dedy Arianto Bannus; Delta Anggelina (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2026)
This community service program was conducted in Marapit Village, Kapuas Tengah District, Kapuas Regency, focusing on the importance of improving human resources through higher education. The program aimed to enhance community awareness and understanding of the strategic role of higher education in improving quality of life and expanding socio-economic opportunities. The implementation methods included educational counseling, religious activities (Persembahyangan Basarah), Dharma Wacana sessions, and the distribution of learning materials and supporting media. This approach integrated educational and religious dimensions as a contextual empowerment strategy. The results indicate an increased understanding among community members, particularly students and parents, regarding higher education as a long-term investment. Furthermore, religious values were strengthened through a deeper understanding of Hindu Kaharingan teachings, contributing to character development and learning motivation among the younger generation. The provision of educational materials and learning media supported program sustainability. Overall, this initiative represents a holistic community empowerment model based on education and spirituality, oriented toward sustainable human resource development. Keywords : Higher Education, Human Resources